Recirculate-based thermoforming compositions

By preparing polypropylene-polyethylene compositions containing recycled polypropylene-polyethylene blends and heterophase propylene copolymers, the performance of the composition is optimized by using Crystex analysis to solve the insufficient performance of polypropylene and polyethylene mixtures in thermoforming. The problem is that a polypropylene-polyethylene composition with high thermal deformation temperature and high Vicar softening temperature is achieved.

CN119213072APending Publication Date: 2024-12-27北欧化工公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380036651.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-09
Filing Date
2023-05-08
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing mixture of polypropylene and polyethylene has problems such as insufficient performance in the thermal forming process, such as fluidity, stiffness, impact strength and thermal deformation temperature. In particular, the temperature stability of the recirculating substance is not suitable, making it difficult to meet the high thermal deformation temperature and High VIKA softening temperature requirements.

Method used

By preparing a polypropylene-polyethylene composition containing 39 to 70% recycled polypropylene-polyethylene blend and 30 to 61% original heterophase propylene copolymer, combined with Crystex analysis measured fractions measured by Crystex analysis and soluble fraction characteristics, optimizing the melt flow rate, tensile modulus and thermal properties of the composition.

Benefits of technology

The high thermal deformation temperature and high Vicar softening temperature of the polypropylene-polyethylene composition are achieved, improving its performance in thermoforming applications and meeting the high demands of fluidity and stiffness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005102855690000121
    Figure BDA0005102855690000121
  • Figure BDA0005102855690000141
    Figure BDA0005102855690000141
  • Figure BDA0005102855690000171
    Figure BDA0005102855690000171
Patent Text Reader

Abstract

A polypropylene-polyethylene composition having a high vicat softening temperature and a high thermal deformation temperature comprising a recycle.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to upgraded polypropylene polyethylene compositions suitable for thermoforming. Background Art

[0002] The mixture of polypropylene and polyethylene (such as the mixture of polypropylene and polyethylene present in commercially available recycled materials) is characterized by limited miscibility. When such mixtures are processed into final products, mechanical and optical properties limit possible applications to ultra-low-cost applications that are not demanding, i.e., applications such as thermoforming that are not demanding. In particular, the temperature stability of recycled materials is generally not suitable. Attempts have been made to at least partially solve these problems by ultra-complex methods (such as the method using calcium carbonate and special additives described in KR10-2184015). It is also known from WO20190224129 that recycled component A (MFR (most) preferably 8 to 12g / 10min) can be blended with original polypropylene component B (MFR2 (most) preferably 0.3 to 0.5g / 10min). Component B can be a random propylene copolymer. However, it is necessary to meet other compositions such as fluidity, stiffness, impact strength, heat deformation temperature and Vicat softening temperature (vicat) in a better way. For given CRYSTEX C2 (CF) and CRYSTEX IV (SF) values, it is particularly desirable to have a high heat distortion temperature and a high Vicat softening temperature. Summary of the invention

[0003] The present invention provides a polypropylene-polyethylene composition having:

[0004] - melt flow rate MFR2 (230°C, ISO1133) of 1.5 to 4.0 g / 10 min;

[0005] - a tensile modulus of at least 1300 MPa measured according to ISO 527-2;

[0006] - the crystalline fraction (CF) is present in an amount ranging from 90.8 to 93.5 wt.-% relative to the total weight of the polypropylene-polyethylene composition, measured according to Crystex analysis, preferably the Crystex analysis described in the description;

[0007] - the soluble fraction (SF) measured according to Crystex analysis, preferably the Crystex analysis described in the description, is present in an amount ranging from 6.5 to 9.2 wt.-% relative to the total weight of the polypropylene-polyethylene composition;

[0008] - the intrinsic viscosity [IV(CF)] of the crystalline fraction measured according to Crystex analysis (preferably the Crystex analysis described in the description) is from 2.3 to 2.9 dl / g;

[0009] - the intrinsic viscosity [IV(SF)] of the soluble fraction measured according to Crystex analysis (preferably the Crystex analysis described in the description) is from 1.80 dl / g to 2.40 dl / g; and

[0010] - the content of units derived from ethylene in the crystalline fraction [C2(CF)] measured according to Crystex analysis (preferably the Crystex analysis described in the description) is from 3.0 to 4.8% by weight;

[0011] Wherein the polypropylene-polyethylene composition comprises a recycle fraction.

[0012] The present invention also provides a blending method for obtaining a polypropylene-polyethylene composition.

[0013] a) 39 to 70 wt. %, preferably 49 to 70 wt. % of a recycled polypropylene-polyethylene blend (A) having:

[0014] - the crystalline fraction (CF) is present in an amount of 89.0 to 92.0 wt.-% relative to the total weight of the recycled polypropylene-polyethylene blend (A) measured according to Crystex analysis, preferably the Crystex analysis described in the description;

[0015] - the soluble fraction (SF) measured according to Crystex analysis (preferably the Crystex analysis described in the description) is present in an amount of 8.0 to 11.0 wt.-% relative to the total weight of the recycled polypropylene-polyethylene blend (A);

[0016] - the intrinsic viscosity [IV(CF)] of the crystalline fraction measured according to Crystex analysis (preferably the Crystex analysis described in the description) is from 1.50 to 1.80 dl / g;

[0017] - the intrinsic viscosity [IV(SF)] of the soluble fraction measured according to Crystex analysis (preferably the Crystex analysis described in the description) is from 0.80 dl / g to 1.80 dl / g; and

[0018] - the content of units derived from ethylene in the crystalline fraction [C2(CF)] measured according to Crystex analysis (preferably the Crystex analysis described in the description) is from 4.0 to 8.0% by weight;

[0019] and

[0020] b) 30 to 61 wt.-%, preferably 30 to 51 wt.-% of an original heterophasic propylene copolymer having:

[0021] - melt flow rate MFR2 (230°C, ISO 1133) of 0.15 to 0.35 g / 10 min;

[0022] - a Young's modulus of at least 1800 MPa, measured in a tensile test according to ISO 527-2 on injection moulded multipurpose specimens prepared according to ISO 527-1;

[0023] - a content of soluble fraction (SF) measured according to Crystex analysis, preferably the Crystex analysis described in the description, of 3.0 to 8.0 wt.-%, based on the total weight of the original heterophasic propylene copolymer; and

[0024] - a total ethylene (C2) content of 0.5 to 3.0 wt.-%, based on the total weight of the original heterophasic propylene copolymer, measured according to Crystex analysis, preferably the Crystex analysis described in the description;

[0025] All amounts are relative to the final resulting polypropylene-polyethylene composition.

[0026] The present invention also relates to thermoformed articles made from the polypropylene-polyethylene compositions described herein.

[0027] Unless otherwise defined, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art to which the invention belongs. Although preferred materials and methods are described herein, any method and material similar or equivalent to those described herein can be used to practice and test the present invention. When describing and claiming the present invention, the following terms will be used according to the definitions as described below. Unless otherwise clearly stated, the terms "a", "a kind of" etc. used refer to more than one / kind.

[0028] For the purposes of this specification, the terms "recycle fraction", "recycle" or "recycle" are used to refer to materials recovered from post-consumer waste and industrial waste, rather than virgin polymers.

[0029] Post-consumer waste refers to items that have completed at least their first use cycle (or life cycle), i.e. have served their first purpose, while industrial waste refers to manufacturing waste that does not normally reach the consumer.

[0030] The term "virgin" refers to newly manufactured materials and / or items prior to first use that have not yet undergone recycling.

[0031] Virgin and recycled materials can be easily distinguished based on the presence or absence of contaminants, such as limonene content, fatty acid content, polyamide content, polystyrene content, talc content and / or chalk content.

[0032] "Recycle fraction" or "recycle" means a fraction or material containing residual amounts of limonene, fatty acids, polyamide, polystyrene, talc and / or chalk. "Residual amount" means a content above the detection limit.

[0033] A polymer blend is a mixture of two or more polymer components. It goes without saying that recyclate is a poor mixture of numerous polymers.

[0034] The CRYSTEX analysis provides excellent and rapid information on the amount of the soluble fraction (SF), the amount of the crystalline fraction (CF) and their intrinsic viscosities ([IV(SF)], [IV(CF)]). The calibration also allows providing the amount of units derived from ethylene in the soluble fraction (SF) and the crystalline fraction (CF), i.e. C2(SF) and C2(CF), respectively.

[0035] The expression "measured according to the Crystex assay, preferably the Crystex assay described in the description" is to be understood as a reference to the experimental part, in particular to the test methods.

[0036] The content of units derived from ethylene [C2(SF)] in the soluble fraction measured according to Crystex analysis (preferably Crystex analysis described in the specification) of the polypropylene-polyethylene composition of the present invention is preferably from 18.0 to 26.0 wt%.

[0037] The polypropylene-polyethylene composition described herein also has one or more of the following:

[0038] (i) a limonene content of 0.1 ppm to 100 ppm as determined by solid phase microextraction (HS-SPME-GC-MS);

[0039] (ii) a fatty acid content of 0.1 to 100 ppm as determined by solid phase microextraction (HS-SPME-GC-MS);

[0040] (iii) a polyamide content of 0.001 to 0.5 wt. % as determined by IR;

[0041] (iv) a polystyrene content of 0.05 to 0.8 wt % as determined by IR;

[0042] (v) a talc content of 0.01 to 0.5% by weight as determined by IR;

[0043] (vi) Chalk content determined by IR of 0.01 to 0.5% by weight.

[0044] It goes without saying that these contaminants arise from the use of the polymer in its "first life": in other words, features (i) to (vi) represent recyclate properties. This is especially true for (i) and (ii), since such contaminants are not used in any virgin material.

[0045] In a preferred aspect, the polypropylene-polyethylene composition of the present invention has:

[0046] - a tensile modulus of at least 1500 MPa measured according to ISO 527-2;

[0047] - the intrinsic viscosity of the soluble fraction [IV(SF)] measured according to Crystex analysis (preferably the Crystex analysis described in the description) is from 1.95 dl / g to 2.40 dl / g;

[0048] - the content of units derived from ethylene [C2(CF)] in the crystalline fraction measured according to Crystex analysis (preferably the Crystex analysis described in the description) is from 3.0 to 3.9% by weight.

[0049] In another preferred aspect, the polypropylene-polyethylene composition of the present invention has:

[0050] - the content of units derived from ethylene in the soluble fraction [C2(SF)] measured according to Crystex analysis (preferably the Crystex analysis described in the description) is from 22.0 to 26.0% by weight.

[0051] The polypropylene-polyethylene composition described herein is preferably obtainable by blending the following components in amounts relative to the final polypropylene-polyethylene composition:

[0052] a) 39 to 70 wt. %, preferably 49 to 70 wt. % of a recycled polypropylene-polyethylene blend (A) having:

[0053] - the crystalline fraction (CF) is present in an amount of 89.0 to 92.0 wt.-% relative to the total weight of the recycled polypropylene-polyethylene blend (A) measured according to Crystex analysis, preferably the Crystex analysis described in the description;

[0054] - the soluble fraction (SF) measured according to Crystex analysis (preferably the Crystex analysis described in the description) is present in an amount of 8.0 to 11.0 wt.-% relative to the total weight of the recycled polypropylene-polyethylene blend (A);

[0055] - the intrinsic viscosity [IV(CF)] of the crystalline fraction measured according to Crystex analysis (preferably the Crystex analysis described in the description) is from 1.50 to 1.80 dl / g;

[0056] - the intrinsic viscosity of the soluble fraction [IV(SF)] measured according to Crystex analysis (preferably the Crystex analysis described in the description) is from 0.80 dl / g to 1.80 dl / g;

[0057] - the content of units derived from ethylene in the crystalline fraction [C2(CF)] measured according to Crystex analysis (preferably the Crystex analysis described in the description) is from 4.0 to 8.0% by weight; and

[0058] - Optionally, the percentage of polyethylene melting enthalpy is lower than 2.5%, preferably lower than 2.1%;

[0059] and

[0060] b) 30 to 61 wt.-%, preferably 30 to 51 wt.-% of an original heterophasic propylene copolymer having:

[0061] - melt flow rate MFR2 (230°C, ISO1133) of 0.15 to 0.35 g / 10 min;

[0062] - a Young's modulus of at least 1800 MPa, measured in a tensile test according to ISO 527-2 on injection moulded multipurpose specimens prepared according to ISO 527-1;

[0063] - a content of soluble fraction (SF) measured according to Crystex analysis, preferably the Crystex analysis described in the description, of 3.0 to 8.0 wt.-%, based on the total weight of the original heterophasic propylene copolymer; and

[0064] - a total ethylene (C2) content of 0.5 to 3.0 wt.-%, based on the total weight of the original heterophasic propylene copolymer, measured according to Crystex analysis, preferably the Crystex analysis described in the description.

[0066] Recycled polypropylene-polyethylene blends (A) are commercially available as required. It is also possible to screen various commercial recycled products and prepare intermediate blends to meet the requirements.

[0067] The recycled polypropylene-polyethylene blend (A) is obtained from recycled waste streams of recycled post-consumer waste or post-industrial waste (e.g. waste from the automotive industry) or a combination of both. Particularly preferably, the polypropylene-polyethylene blend (A) consists of recycled post-consumer waste and / or post-industrial waste.

[0068] On the one hand, polypropylene-polyethylene blend (A) can be a material rich in polypropylene (PP) of recycled plastic material, which comprises significantly more polypropylene than polyethylene. Waste streams recycled with a high content of polypropylene can be obtained from, for example, the automotive industry, especially because some automotive parts (e.g., bumpers) are sources of fairly pure polypropylene materials in the recycling stream or by intensive sorting. The material rich in polypropylene can be obtained by selective processing, degassing and filtering and / or by separation according to type and color (e.g., NIR or Raman sorting and VIS sorting). It can be obtained from household waste streams (i.e., it is a product of household recycling), such as the "yellow bag" recycling system organized under the "green dot" organization operating in parts of Germany.

[0069] Preferably, the polypropylene-polyethylene blend (A) is obtained from recycled waste by plastic recycling methods known in the art. The polypropylene-polyethylene blend (A) used herein is commercially available, for example, from Corepla (Italian Federation for the Collection, Recovery and Recycling of Packaging Plastic Waste), Resource Plastics Corp. (Brampton, ON), Steinbeis PolyVert, Plastics and Recycling (Austria), Vogt Plastik GmbH (Germany), MtmPlastics GmbH (Germany), etc. Non-exhaustive examples of recycled materials rich in polypropylene include: PP, PP (Mtm Plastics GmbH), Kruplene-C PP (Steinbeis PolyVert), Systalen PP (Systec Plastics GmbH), Recycled polypropylene granules (Axion Ltd) and polypropylene copolymers (BSP Compounds). A particularly suitable polypropylene-polyethylene blend (A) is "Kruplene-C chalk white 10.1-15.0", which is also sold by Steinbeis Polyvert as "Steinbeis rPP" or "Steinbeis rPP C chalk white 10.1-15.0".

[0070] The pristine heterophasic propylene copolymers as blend partners required herein may also be commercially available. A preferred pristine heterophasic propylene copolymer is Borealis BA2000.

[0071] Particularly preferably, the pristine heterophasic propylene copolymer has a Charpy notched impact strength (1eA) (non-instrumented, ISO 179-1, +23°C) of at least 27 kJ / m 2The Charpy notched impact strength (1eA) (non-instrumented, ISO 179-1, +23°C) is preferably 28 to 34 kJ / m 2 .

[0072] The preferred polypropylene-polyethylene composition as described above can be obtained by blending the following components in amounts relative to the final polypropylene-polyethylene composition:

[0073] a) 39 to 70 wt. %, preferably 49 to 70 wt. % of a recycled polypropylene-polyethylene blend (A) having:

[0074] - the crystalline fraction (CF) is present in an amount of 89.0 to 90.7 wt.-% relative to the total weight of the recycled polypropylene-polyethylene blend (A) measured according to Crystex analysis, preferably the Crystex analysis described in the description;

[0075] - the soluble fraction (SF) measured according to Crystex analysis, preferably the Crystex analysis described in the description, is present in an amount of 9.3 to 11.0 wt.-% relative to the total weight of the recycled polypropylene-polyethylene blend (A);

[0076] - the intrinsic viscosity of the soluble fraction [IV(SF)] measured according to Crystex analysis (preferably the Crystex analysis described in the description) is from 1.60 dl / g to 1.80 dl / g;

[0077] - the content of units derived from ethylene [C2(CF)] in the crystalline fraction, measured according to Crystex analysis (preferably the Crystex analysis described in the description), is from 4.0 to 4.7% by weight; and

[0078] - Optionally, the percentage of polyethylene melting enthalpy is less than 2.1%;

[0079] and

[0080] b) 30 to 61 wt.-%, preferably 30 to 51 wt.-% of an original heterophasic propylene copolymer having:

[0081] - melt flow rate MFR2 (230°C, ISO1133) of 0.15 to 0.35 g / 10 min;

[0082] - a Young's modulus of at least 1800 MPa, measured in a tensile test according to ISO 527-2 on injection moulded multipurpose specimens prepared according to ISO 527-1;

[0083] - Charpy notched impact strength (1eA) (non-instrumented, ISO 179-1, +23°C) of at least 27 kJ / m 2 ;

[0084] - a content of soluble fraction (SF) measured according to Crystex analysis, preferably the Crystex analysis described in the description, of 3.0 to 8.0 wt.-%, based on the total weight of the original heterophasic propylene copolymer; and

[0085] - a total ethylene (C2) content of 0.5 to 3.0 wt.-%, measured according to Crystex analysis (preferably the Crystex analysis described in the description).

[0086] Those skilled in the art will appreciate that for the recyclate, i.e. the polypropylene-polyethylene blend (A), it is beneficial to:

[0087] a) a relatively high crystalline fraction (CF) is present in an amount of 89.0 to 90.7 wt.-% relative to the total weight of the recycled polypropylene-polyethylene blend (A) as measured according to Crystex analysis, preferably the Crystex analysis described in the description;

[0088] b) the intrinsic viscosity of the relatively high soluble fraction [IV(SF)] measured according to Crystex analysis (preferably the Crystex analysis described in the specification) is from 1.60 dl / g to 1.80 dl / g;

[0089] c) the content of units derived from ethylene [C2(CF)] in the relatively low crystalline fraction, measured according to Crystex analysis (preferably the Crystex analysis described in the description), is from 4.0 to 4.7% by weight.

[0090] Furthermore, the polyethylene melting enthalpy percentage of the polypropylene-polyethylene blend (A) is below 2.5%, preferably below 2.1%, most preferably below 2.0% by weight.

[0091] It will be further appreciated by the skilled person that the pristine heterophasic propylene copolymer as used herein is characterised by a relatively low soluble fraction (SF) content of 3.0 to 8.0 wt.-% as measured according to Crystex analysis, preferably the Crystex analysis as described in the description; and that the pristine heterophasic propylene copolymer as used herein is further characterised by a relatively low total ethylene (C2) content of 0.5 to 3.0 wt.-% as measured according to Crystex analysis, preferably the Crystex analysis as described in the description.

[0092] In another preferred aspect, the polypropylene-polyethylene compositions described herein are further characterized by the following inequality:

[0093] -1.96*C2(CF)[wt%]+12.13*IV(SF)[dl / g]>96

[0094] and / or

[0095] -0.32*C2(CF)[wt%]+9.5*IV(SF)[dl / g]>151.5

[0096] In yet another aspect, the present invention relates to a blending process for obtaining a polypropylene-polyethylene composition:

[0097] a) 39 to 70 wt. %, preferably 49 to 70 wt. % of a recycled polypropylene-polyethylene blend (A) having:

[0098] - the crystalline fraction (CF) is present in an amount of 89.0 to 92.0 wt.-% relative to the total weight of the recycled polypropylene-polyethylene blend (A) measured according to Crystex analysis, preferably the Crystex analysis described in the description;

[0099] - the soluble fraction (SF) measured according to Crystex analysis (preferably the Crystex analysis described in the description) is present in an amount of 8.0 to 11.0 wt.-% relative to the total weight of the recycled polypropylene-polyethylene blend (A);

[0100] - the intrinsic viscosity [IV(CF)] of the crystalline fraction measured according to Crystex analysis (preferably the Crystex analysis described in the description) is from 1.50 to 1.80 dl / g;

[0101] - the intrinsic viscosity of the soluble fraction [IV(SF)] measured according to Crystex analysis (preferably the Crystex analysis described in the description) is from 0.80 dl / g to 1.80 dl / g;

[0102] - the content of units derived from ethylene in the crystalline fraction [C2(CF)] measured according to Crystex analysis (preferably the Crystex analysis described in the description) is from 4.0 to 8.0% by weight;

[0103] and

[0104] b) 30 to 61 wt.-%, preferably 30 to 51 wt.-% of an original heterophasic propylene copolymer having:

[0105] - melt flow rate MFR2 (230°C, ISO 1133) of 0.15 to 0.35 g / 10 min;

[0106] - a Young's modulus of at least 1800 MPa, measured in a tensile test according to ISO 527-2 on injection moulded multipurpose specimens prepared according to ISO 527-1;

[0107] - a content of soluble fraction (SF) measured according to Crystex analysis, preferably the Crystex analysis described in the description, of 3.0 to 8.0 wt.-%, based on the total weight of the original heterophasic propylene copolymer; and

[0108] - a total ethylene (C2) content of 0.5 to 3.0 wt.-%, based on the total weight of the original heterophasic propylene copolymer, measured according to Crystex analysis, preferably the Crystex analysis described in the description;

[0109] All amounts are relative to the final resulting polypropylene-polyethylene composition.

[0110] The blending is usually carried out using an extruder in the presence of a stabilizer package, such as known in the art. In this process, the Charpy notched impact strength (1eA) (non-instrumented, ISO 179-1, +23°C) of the pristine heterophasic propylene copolymer is preferably at least 20 kJ / m 2 All ranges described above with respect to the composition also apply to the method.

[0111] The original heterophasic polypropylene copolymer will be described in more detail below.

[0112] The original heterophasic propylene copolymer comprises as polymer components a polypropylene matrix (M) and an elastomeric copolymer (EPC). In one embodiment the at least one heterophasic propylene copolymer (HECO) comprises as (semi-crystalline) matrix a propylene homopolymer (PPH) and as elastomeric propylene copolymer (EPC) a propylene-ethylene rubber.

[0113] The polypropylene matrix (M) is preferably a random propylene copolymer or a propylene homopolymer, the latter being particularly preferred. The expression "propylene homopolymer" relates to a polypropylene consisting of more than 99.5 wt.-%, preferably more than or at least 99.7 wt.-% propylene units. In a preferred embodiment, only propylene units can be detected in the propylene homopolymer.

[0114] The elastomeric propylene copolymer (EPC) comprises units derived from propylene and ethylene and / or C4 to C20 α-olefins, more preferably derived from ethylene and / or C4 to C10 α-olefins, most preferably derived from ethylene, C4, C6 and / or C8 α-olefins (e.g. ethylene), and optionally units derived from a conjugated diene.

[0115] The pristine heterophasic propylene copolymer preferably has a total ethylene (C2) content of 0.5 to 3.0 wt.-%, more preferably 0.9 to 2.5 wt.-%, most preferably 1.0 to 2.0 wt.-%, measured according to Crystex analysis (preferably Crystex analysis as described in the description).

[0116] The original heterophasic propylene copolymer preferably has a content of soluble fraction (SF) measured according to Crystex analysis, preferably the Crystex analysis described in the description, based on the total weight of the original heterophasic propylene copolymer of 3.0 to 8.0 wt.-%, more preferably 4.0 to 7.0 wt.-%, most preferably 5.0 to 6.0 wt.-%.

[0117] The ethylene content of the soluble fraction (SF) measured according to Crystex analysis (preferably Crystex analysis as described in the description) of the original heterophasic propylene copolymer (C2(SF)) is preferably from 10.0 to 30.0 wt.-%, more preferably from 15.0 to 25.0 wt.-%, most preferably from 18.0 to 22.0 wt.-%.

[0118] The intrinsic viscosity (iV(SF)) of the soluble fraction (SF) of the original heterophasic propylene copolymer (HECO-1) is preferably not more than 4.0 dl / g, more preferably from 3.0 to 4.0 dl / g, even more preferably from 3.2 to 3.9 dl / g, like 3.5 dl / g.

[0119] The original heterophasic propylene copolymer (HECO-1) preferably has an ethylene content (C2(CF)) of the crystalline fraction (CF) measured according to Crystex analysis, preferably Crystex analysis as described in the description, of 0.1 to 2.0 wt.-%, more preferably of 0.2 to 1.0 wt.-%, most preferably of 0.3 to 0.5 wt.-%.

[0120] It is to be understood that the present polypropylene polyethylene composition may comprise not only one, but two original heterophasic propylene copolymers having different melt flow rates. This allows to tailor the melt flow rate of the final polyolefin composition.

[0121] The at least one pristine heterophasic propylene copolymer has an impact strength (ISO 179-1, Charpy 1eA + 23°C) of at least 17 kJ / m 2 , more preferably at least 19 kJ / m 2 , and more preferably at least 20 kJ / m 2 , especially 15 to 40 kJ / m 2 , more particularly 17 to 38 kJ / m 2 , further particularly 20 to 36 kJ / m 2 .

[0122] The pristine heterophasic propylene copolymer may have a tensile Young's modulus measured according to ISO 527-2 of at least 1800 MPa, preferably at least 1830 MPa, like from 1800 to 2100 MPa, preferably from 1830 to 2050 MPa.

[0123] The yield strength of the original heterophasic propylene copolymer (Heco-1) may preferably be from 30 to 40 MPa, more preferably from 33 to 37 MPa and the strain at break independent of the yield strength is preferably from 40 to 50 %, more preferably from 44 to 46 %.

[0124] The present invention also relates to thermoformed articles made from the polypropylene-polyethylene composition described herein. Likewise, all preferred aspects and ranges disclosed for the composition also apply to the thermoformed articles. The thermoformed articles made from the polypropylene-polyethylene composition described herein preferably contain the polypropylene-polyethylene composition, and the amount of the polypropylene-polyethylene composition relative to the article is at least 97.0% by weight, more preferably at least 98.0% by weight, and most preferably at least 98.5% by weight.

[0125] Experimental Section

[0126] The following examples are included to illustrate certain aspects and embodiments of the invention described in the claims. However, it should be understood by those skilled in the art that the following description is merely illustrative and should not be taken in any way as limiting the invention.

[0127] Test Method

[0128] a) CRYSTEX

[0129] Determination of the crystalline and soluble fractions and their respective properties (IV and ethylene content)

[0130] The crystalline fraction (CF) and soluble fraction (SF) of the polypropylene (PP) composition and the comonomer content and intrinsic viscosity of each part are analyzed using the Crystex (crystallization extraction) method. Possible instruments that can be used are Crystex QC or Crystex 42 (Polymer Char; Valencia, Spain). Detailed information on the technology and method can be found in the literature (Ljiljana Jeremic, Andreas Albrecht, Martina Sandholzer & Markus Gahleitner (2020) Rapid characterization of high-impact ethylene-propylene copolymer composition by crystallization extraction separation: comparability to standard separation methods, International Journal of Polymer Analysis and Characterization, 25: 8, 581-596).

[0131] The crystalline and non-crystalline fractions were separated by temperature cycles of dissolution at 160° C., crystallization at 40° C. and redissolution in 1,2,4-trichlorobenzene at 160° C. Quantification of SF and CF as well as determination of the ethylene content (C2) were achieved by an integrated infrared detector (IR4), and the intrinsic viscosity (IV) was determined using an online 2-capillary viscometer.

[0132] The IR4 detector is a multi-wavelength detector that measures two different bands (CH3 stretching vibration (centered at about 2960 cm -1 ) and CH stretching vibration (2700-3000cm -1 )) is used to determine the concentration and ethylene content in ethylene-propylene copolymers. The IR4 detector is used with a series of 8 EP copolymers with known ethylene contents ranging from 2 wt % to 69 wt % (by 13 C-NMR measurement), each at a variety of concentrations ranging from 2 mg / ml to 13 mg / ml) were calibrated. In order to simultaneously meet the characteristics, concentrations and ethylene content of various polymer concentrations expected during Crystex analysis, the following calibration formula was used:

[0133] Concentration = a + b * absorbance (CH) + c * (absorbance (CH))2 + d * absorbance (CH3) + e * (absorbance (CH3)2 + f * absorbance (CH) * absorbance (CH3) (Formula 1)

[0134] CH3 / 1000C=a+b*absorbance(CH3)+c*absorbance(CH3)+d*(absorbance(CH3) / absorbance(CH3))+e*(absorbance(CH3) / absorbance(CH3))2(Formula 2)

[0135] Constants a to e of Formula 1 and constants a to f of Formula 2 are determined by using least squares regression analysis.

[0136] The CH3 / 1000C is converted to ethylene content (in weight %) using the following relationship:

[0137] Weight % (ethylene in EP copolymer) = 100 - CH3 / 1000TC*0.3 (Formula 3)

[0138] The amounts of soluble fraction (SF) and crystalline fraction (CF) are related by XS calibration to the amount of "xylene cold solubles" (XCS) and "xylene cold insolubles" (XCI) fraction respectively determined gravimetrically according to ISO 16152. The XS calibration is achieved by testing various EP copolymers with XS contents ranging from 2 to 31 wt%. A linear calibration curve is used.

[0139] The intrinsic viscosity (IV) of the parent EP copolymer and its soluble and crystalline fractions was determined using an online 2-capillary viscometer and correlated to the corresponding IV determined by the standard method in decalin according to ISO 1628-3. Calibration was achieved using various EP PP copolymers with IV = 2-4 dL / g. The calibration curve determined was linear.

[0140] The samples to be analyzed were weighed at a concentration of 10 to 20 mg / ml. To avoid injection of gels and / or polymers (such as PET and PA) that may not dissolve in TCB at 160°C, the weighed samples were loaded into a stainless steel mesh (MW 0,077 / D 0,05 mm).

[0141] After automatically filling the vials with 1,2,4-TCB containing 250 mg / l 2,6-tert-butyl-4-methylphenol (BHT) as an antioxidant, the samples were dissolved at 160 °C until completely dissolved, typically for 60 min, with constant stirring or gentle shaking. To avoid sample degradation, the polymer solution was covered with a N2 atmosphere during the dissolution process.

[0142] A certain volume of sample solution is injected into a column filled with an inert carrier, where crystallization of the sample and separation of the soluble fraction from the crystalline fraction is performed. This process is repeated twice. During the first injection, the entire sample is measured at high temperature, and IV [dl / g] and C2 [wt%] of the PP composition are determined. During the second injection, the soluble fraction (at low temperature) and the crystalline fraction (at high temperature) of the crystallization cycle are measured (wt% SF, wt% C2, IV).

[0143] b) Determination of the amount of "iPP", "PVC", "PA", "PET", "PS" and "PE" by transmission infrared spectroscopy

[0144] Sample preparation:

[0145] All calibration samples and samples to be analyzed were prepared in a similar manner on fused pressed plaques.

[0146] About 2 to 3 g of the compound to be analyzed are melted at 190°C. Subsequently, a pressure of 60 to 80 bar is applied in a hydraulic hot press for 20 seconds. Next, the sample is cooled to room temperature in a cold press under the same pressure within 40 seconds to control the morphology of the compound. The thickness of the plate is controlled by a 2.5 cm x 2.5 cm, 100 to 200 μm thick metal calibration frame plate (depending on the MFR of the sample); two plates are made in parallel at the same time and under the same conditions. The thickness of each plate is measured before any FTIR measurement is performed; the thickness of all plates is between 100 and 200 μm.

[0147] To control the plate surface and avoid any disturbance during the measurements, all plates were pressed between two sheets of double-sided silicone release paper.

[0148] In case of powder samples or heterogeneous compounds, the pressing process will be repeated three times to increase homogeneity by pressing and cutting the samples under the same conditions as before.

[0149] Spectrometer:

[0150] Use a standard transmission FTIR spectrometer, such as a Bruker Vertex 70 FTIR spectrometer, with the following settings:

[0151] Spectral range: 4000-400cm -1 ,

[0152] The aperture is 6mm,

[0153] Spectral resolution is 2cm -1 ,

[0154] 16 background scans, 16 spectrum scans,

[0155] The interference pattern zero filling factor is 32,

[0156] ·Norton Beer strong cut toe.

[0157] Spectra were recorded and analyzed in Bruker Opus software.

[0158] Calibration samples:

[0159] Since FTIR is a secondary method, several calibration standards are mixed to cover the target analysis range, typically:

[0160] 0.2 wt% to 2.5 wt% of PA,

[0161] 0.1 to 5 wt% of PS,

[0162] 0.2 to 2.5 wt% of PET,

[0163] · 0.1 to 4 wt% of PVC.

[0164] The following commercial materials were used as compounds: Borealis HC600TF as iPP, Borealis FB3450 as HDPE, RAMAPET N1S (Indorama Polymer) for PET, B36LN (BASF), Styrolution PS 486N (Ineos) for high impact polystyrene (HIPS), and Inovyn PVC 263B (powder form) for PVC.

[0165] All compounds were prepared on a small scale in a Haake kneader at temperatures below 265°C for less than 10 minutes to avoid degradation.

[0166] Additional antioxidants such as Irgafos 168 (3000 ppm) were added to minimize degradation.

[0167] calibration:

[0168] The FTIR calibration principle is the same for all components: the intensity of a specific FTIR band divided by the plate thickness is the same as the intensity of the 1 H or 13 C solution NMR determination of the amount of components.

[0169] Each specific FTIR absorption band is chosen because its intensity increases with increasing component concentration and is isolated from the rest of the peaks, regardless of the composition of the calibration standards and actual samples.

[0170] This method is described in a publication by Signoret et al. (“Alterations of plastic spectra in MIR and the potential impacts on identification towards recycling”, Resources, conservation and Recycling journal, Vol. 161, Article No. 104980, 2020).

[0171] The wavelength of each calibration band is:

[0172] PA 3300cm -1 ,

[0173] PS 1601cm -1 ,

[0174] PET: 1410cm -1 ,

[0175] PVC 615cm -1 ,

[0176] ·1167cm of iPP -1 .

[0177] A linear calibration (linearity based on the Beer-Lambert law) is constructed for each polymer component i. A typical linear correlation for such a calibration is shown below:

[0178]

[0179] In the formula, x i is the fraction of polymer component i (in weight %)

[0180] E i is the absorbance intensity of the specific bands associated with polymer component i (in au (absorbance units)). These specific bands are: 3300 cm for PA -1 , PS 1601cm -1 , PET 1410cm -1 , PVC 615cm -1 , iPP 1167cm -1 .

[0181] d is the thickness of the sample plate.

[0182] A i and B i are the two correlation coefficients determined for each calibration curve.

[0183] No specific isolated band was found for the C2-enriched fraction, so the C2-enriched fraction was estimated indirectly:

[0184] x Rich in C2 =100-(x iPP +x PA +x PS +x PET +x EVA +x PVC +xChalk +xTalc)

[0185] The contents of EVA, chalk and talc are estimated as "semi-quantitative". This therefore makes the C2-rich content "semi-quantitative".

[0186] The following bands are used to estimate the content of EVA, chalk and talc:

[0187] EVA: Band center at 607cm -1

[0188] Chalk: band centred at 1798cm -1

[0189] Talc: The band center is at 3676cm -1 .

[0190] In addition, the presence of titanium dioxide, TiO2 and carbon black was reported. Their quantification could not be performed using FTIR.

[0191] For each calibration standard (when available), the amount of each component is given by 1 H or 13 C solution state NMR determination, which is the primary method (except PA). The NMR measurements are performed on exactly the same FTIR plate used to construct the FTIR calibration curve.

[0192] c) Quantification of microstructure by NMR spectroscopy

[0193] Quantitative nuclear magnetic resonance (NMR) spectroscopy was used to quantify the ethylene content of the polymers.

[0194] The Bruker Avance Neo 400 NMR spectrometer was used to 1 H and 13 C were operated at 400.15 and 100.62 MHz, respectively, and quantitative data were recorded in solution. 13 C{ 1 H} NMR spectra. All spectra were obtained using 13 C optimized 10mm extension temperature probe was recorded at 125°C, and nitrogen was used for all pneumatic devices. About 200mg of material was dissolved in about 3ml of 1,2-tetrachloroethane-d2 (TCE-d2) together with about 3mg of BHT (2,6-di-tert-butyl-4-methylphenol, CAS128-37-0) and chromium (III) acetylacetonate (Cr(acac)3) to obtain a 60mM relaxation agent solution in solvent as described in "G. Singh, A. Kothari, V. Gupta, Polymer Testing 2009, 28(5), 475".

[0195] To ensure that the solution is uniform, the NMR tube is reheated in a rotary furnace for at least 1 hour after initial sample preparation in the heating zone. After the tube is inserted into the magnet, it is rotated at 10 Hz. This setting is selected mainly for the quantitative needs of high resolution and accurate quantification of ethylene content. Standard single pulse excitation without NOE is used, with optimized tip angle, 1 s cycle delay and double-stage WALTZ16 decoupling scheme, as described in "Z. Zhou, R. Kuemmerle, X. Qiu, D. Redwine, R. Cong, A. Taha, D. Baugh, B. Winniford, J. Mag. Reson. 187 (2007) 225 and V. Busico, P. Carbonniere, R. Cipullo, C. Pellecchia, J. Severn, G. Talarico, Macromol. Rapid Commun. 2007, 28, 1128". A total of 6144 (6k) transient values ​​are obtained for each spectrum.

[0196] Quantitative 13 C{ 1 The H} NMR spectra were processed, integrated and the relevant quantitative properties were determined from the integration. All chemical shifts were indirectly referenced to the central methylene of the ethylene block (EEE) at 30.00 ppm using the chemical shift of the solvent. This method allows for comparable references even in the absence of this structural unit.

[0197] Characteristic signals corresponding to ethylene incorporation were observed (as described in "Cheng, HN, Macromolecules 1984, 17, 1950") and the comonomer fraction was calculated as the fraction of ethylene in the polymer relative to all monomers in the polymer:

[0198] fE=(E / (P+E))

[0199] Using the method of WJ. Wang and S. Zhu (Macromolecules 2000, 33 1157), 13 C{ 1 The comonomer fraction is quantified by integrating multiple signals across the spectral region in the H} spectrum. The integration region is adjusted slightly to improve applicability over the entire range of comonomer content encountered.

[0200] The mole percentage of comonomer incorporation is calculated from the mole fraction:

[0201] E[mol%]=100*fE

[0202] The weight percent of comonomer incorporation is calculated from the mole fraction:

[0203] E[weight%]=100*(fE*28.06) / ((fE*28.06)+((1-fE)*42.08))

[0204] d) Heat Deflection Temperature (HDT) ISO 75-Method B:

[0205] HDT is determined according to ISO 75 method B on samples of 80 mm x 10 mm x 4 mm. The test samples are injection molded according to ISO19069-2. The samples are loaded in a three-point bending apparatus. The samples are loaded so that the external fiber stress is 0.45 MPa. The temperature is increased at a constant heating rate of 120°C / h until the external fiber strain reaches 0.2%. The temperature corresponding to this deformation is the heat deformation temperature.

[0206] e) Vicat softening temperature (method A-50)

[0207] Vicat softening temperature (VST) tests were performed according to ISO 306 method using a load of 10 N and a heating rate of 50 °C / h. The dimensions of the test specimens were 10 mm x 10 mm x 4 mm. B-type bars (ISO 20753) (80 mm x 10 mm x 4 mm) were injection molded according to ISO 19069-2. The test specimens were milled from the center of the B-type bars to final size.

[0208] f) Fabrication of Multi-Purpose Samples (MPS) and Charpy Type 1 Samples

[0209] All MPS were manufactured by injection molding according to ISO 3167 (Plastics - Multipurpose test specimens) and ISO 19069 2 (Plastics - Polypropylene (PP) molding and extrusion materials - Part 2: Preparation of test specimens and determination of properties) on an Engel Victory 60 (Engel, Austria). The samples were conditioned at 23°C and 50% relative humidity for at least three days. After conditioning, these specimens were used for tensile tests. Type 1 specimens for Charpy notched impact testing were prepared by injection molding according to ISO 19069-2:2016 and conditioned at 23°C and 50% relative humidity for at least three days before testing.

[0210] g) Melt flow rate (MFR)

[0211] The MFR measurement was carried out on a Zwick / Roell Mflow melt flow indexer (Zwick Roell, Germany) at 230°C and 2.16 kg according to ISO 1133-1 (Plastics - Determination of melt mass flow rate (MFR) and melt volume flow rate (MVR) of thermoplastics - Part 1: Standard method). The piston was cut every 3 mm. The time between cuts was measured and each extrudate was weighed on an ABS220-4 electronic balance (Kern & Sohn, Germany). The MFR (in g / 10 min) for each cut was calculated by extrapolation to 10 minutes. One measurement was performed for each material. Six cuts were performed in one measurement and used to calculate the average and standard deviation.

[0212] h) Density

[0213] Density measurements were performed according to ISO 01183-1 (Plastics - Determination of density of non-foamed plastics - Part 1: Immersion method, liquid pycnometer method and titration method) using a Sartorius CPA 225D laboratory balance (Sartorius, Germany). The samples were cut from the gate-side shoulder of the multi-purpose sample (MPS). In the first step, the corresponding samples were weighed dry and their mass in air (m S,A In the second step, the sample is immersed in deionized water with added detergent and placed under a buoyancy cage connected to a balance, enabling the measurement of sample buoyancy (m) without the need for a sinker. S.IL ). Use a wire to release the bubbles in the sample and record the temperature of the immersion liquid to calculate its density (ρ IL The sample density is calculated using the following formula using the measurement device correction variables A and B:

[0214]

[0215] For each material, five samples (each cut from a single MPS) were used to calculate the mean and standard deviation.

[0216] i) Differential Scanning Calorimetry (DSC)

[0217] DSC tests were performed on a Perkin Elmer differential scanning calorimeter DSC 8500 (PerkinElmer, USA). Samples were cut from the shoulders of injection molded multipurpose samples and packaged in perforated aluminum pans. The average sample weight was about 5 mg. The program included a first heating, subsequent cooling, and a second heating stage, with a temperature range of 0°C to 200°C for each stage, a constant heating / cooling rate of 10K / min, nitrogen as a purge gas, and a flow rate of 20 ml / min. DSC measurements were completed to determine the melting peak of the second heating stage, which is a feature of the semi-crystallinity achieved under controlled cooling in the DSC device. In order to determine the melting enthalpy, the area of ​​the melting peak was integrated. Since the heat flux was normalized by the sample mass, the thermogram can be displayed as a normalized heat flux (W / g) over time, and the peak area (W / g*s) will be calculated as W*s / g or J / g normalized melting enthalpy. For each material, five samples (each cut from a single MPS) were used to calculate the average and standard deviation. The measurements were performed according to ISO 11357-1 (Plastics - Differential Scanning Calorimetry (DSC) - Part 1: General principles) and ISO 11357-3 (Part 3: Determination of temperature and enthalpy of melting and crystallization). Briefly, the melting peak area in the second heating result was integrated.

[0218] The percentage of melting enthalpy of polyethylene is calculated as follows:

[0219] The percentage (%) of PE melting enthalpy = 100*PE melting enthalpy / (PE melting enthalpy + PP melting enthalpy).

[0220] j) Oxidation induction temperature (T OX )

[0221] The oxidation induction temperature (dynamic OIT) was characterized using a DSC 4000 differential thermal analysis (DTA) instrument (PerkinElmer, USA) according to ISO 11357-6 (Plastics - Differential Scanning Calorimetry (DSC) - Part 6: Determination of the oxidation induction time (isothermal OIT) and the oxidation induction temperature (dynamic OIT)). The samples were cut from the shoulders of the injection molded MPS and packaged in perforated aluminum pans. The average sample weight was about 5 mg. A single heating step was performed between 23°C and 300°C at a heating rate of 10 K / min, with synthetic air as the purge gas at a flow rate of 20 ml / min. The intersection of the slopes before and during oxidation gives the oxidation start or oxidation induction temperature (in °C). For each material, five samples (each cut from a single MPS) were used to calculate the average and standard deviation.

[0222] k) Tensile properties

[0223] Mechanical properties (Young's modulus, yield strength and strain at break) were examined using a universal testing machine Zwick AllroundLine Z020 (Zwick Roell, Germany) equipped with a multi-extensometer at 23°C. Test parameters and MPS were used according to ISO527-1 (Plastics - Determination of tensile properties - Part 1: General principles) and ISO 527-2 (Part 2: Test conditions for molded and extruded plastics), with a moving speed of 1 mm / min for Young's modulus determination until the strain was 0.25%, then 50 mm / min until failure. Five MPS were tested for each material to calculate the average and standard deviation.

[0224] L) Charpy notched impact strength

[0225] Impact tests were performed according to ISO 179-1 (Plastics - Determination of Charpy impact properties - Part 1: Non-instrumented impact test) on a Zwick / Roell HIT25P pendulum impact tester (Zwick Roell, Germany) using injection molded samples (see information below). After preliminary tests to determine the appropriate pendulum size, a suitable pendulum was selected to test each corresponding material. The notch was made with a Leica RM2265 microtome (Leica, Germany) and measured on an Olympus SZX16 stereo microscope (Olympus, Japan). The test conditions were 23°C and edge notched samples with a notch radius of 0.25 mm (1eA) were used. Ten samples of each material were tested to calculate the average and standard deviation.

[0226] m) Limonene measurement

[0227] Limonene was quantified using solid phase microextraction (HS-SPME-GC-MS) by the standard addition method.

[0228] 50 mg of ground sample was weighed into a 20 ml headspace vial and after adding different concentrations of limonene and a glass coated magnetic stirring bar, the vial was closed with a magnetic cap lined with silicone / PTFE. Diluted limonene standards of known concentrations were added to the samples using a microcapillary (10 pL). 0, 2, 20 and 100 ng (equivalent to 0 mg / kg, 0.1 mg / kg, 1 mg / kg and 5 mg / kg) of limonene were added, and in addition, 6.6 mg / kg, 11 mg / kg and 16.5 mg / kg standard amounts of limonene were combined with some of the samples tested in this application. For quantification, ion 93 obtained in SIM mode was used. Enrichment of the volatile portion was performed by headspace solid phase microextraction using a 2 cm stable flexible 50 / 30 pm DVB / Carboxen / PDMS fiber at 60°C for 20 minutes. Desorption was performed directly at the heated injection port of the GCMS system at 270°C.

[0229] GCMS parameters:

[0230] Chromatographic column: 30m HP 5MS 0.25*0.25;

[0231] Injector: splitless, with 0.75 mm SPME liner, 270 °C;

[0232] Temperature program: -10°C (1 min);

[0233] Carrier gas: Helium 5.0, linear velocity 31 cm / s, constant flow;

[0234] MS: single quadrupole, direct interface, interface temperature 280 °C;

[0235] Acquisition: SIM scanning mode;

[0236] Scan parameters: 20-300amu;

[0237] SIM parameters: m / Z 93, 100 ms dwell time.

[0238] n) Total free fatty acid content

[0239] Fatty acid quantification was performed using headspace solid phase microextraction (HS-SPME-GC-MS) by the standard addition method.

[0240] 50 mg of ground sample was weighed into a 20 ml headspace vial and after adding different concentrations of limonene and a glass-coated magnetic stirring bar, the vial was closed with a magnetic cap lined with silicone / PTFE. A 10 μL microcapillary was used to add known concentrations of a diluted free fatty acid mixture (acetic acid, propionic acid, butyric acid, valeric acid, hexanoic acid and octanoic acid) standard to the sample at three different levels. Each individual acid was added at 0, 50, 100 and 500 ng (equivalent to 0 mg / kg, 1 mg / kg, 2 mg / kg and 10 mg / kg). For quantification, ion 60 obtained in SIM mode was used for all acids except propionic acid (ion 74 was used here).

[0241] GCMS parameters:

[0242] Chromatographic column: 20m ZB Wax plus 0.25*0.25;

[0243] Injector: 5:1 split, with glass-lined split liner, 250°C;

[0244] Temperature program: 40°C (1 min) @ 6°C / min to 120°C, @ 15°C to 245°C (5 min);

[0245] Carrier gas: Helium 5.0, linear velocity 40 cm / s, constant flow;

[0246] MS: single quadrupole, direct interface, interface temperature 220 °C;

[0247] Acquisition: SIM scanning mode;

[0248] Scan parameters: 46-250 amu 6.6 scans / s;

[0249] SIM parameters: m / z 60, 74, 6.6 scans / s.

[0250] experiment

[0251] Commercially available polypropylene-polyethylene blends (A) were used. Table 1 provides a summary of polypropylene-polyethylene blends (A) #1, #2 and #3.

[0252] Table 1: Overview of polypropylene-polyethylene blends (A)

[0253]

[0254] The commercially available original heterophasic propylene copolymer (Borealis HECO BA2000) has an MFR2 of 0.23 g / 10 min, a Young's modulus of 1850 MPa, and a Charpy NIS (23°C) of 33 kJ / m 2 , the total amount of ethylene was 1.35 wt. % and the amount of CRYSTEX soluble fraction was 5.6 wt. %. Table 2 provides an overview.

[0255] Table 2: Properties of original heterophasic propylene copolymers

[0256] Original heterophasic propylene copolymer MFR (230℃ / 2.16kg) [g / 10min] 0.23 Young's modulus [MPa] 1850 <![CDATA[Charpy NIS [kJ / m 2 at 23 °C]]> 33 Crystex_C2 (weight %) 1.35 Crystex_C2 crystalline fraction (wt%) 0.3 Crystex_C2 soluble fraction (wt%) 19.0 Crystex crystalline fraction (CF) (wt%) 94.4 Crystex_IV(dL / g) 4.05 Crystex_IV crystalline fraction (dL / g) 4.02 Crystex_IV soluble fraction (dL / g) 3.54 Crystex soluble fraction (SF) (wt%) 5.6

[0257] Commercial polypropylene-polyethylene blends (A) #1 to #3 were blended with the commercial virgin heterophasic propylene copolymer, all blends were mixed with 0.15 wt% Irganox 1010 and 0.15 wt% Irgafos 168. Table 3 reports the amounts used for the compositions.

[0258] Table 3: Summary of composition

[0259]

[0260] Table 4 reports the parameters measured for the resulting compositions.

[0261] Table 4: Summary of the resulting compositions

[0262]

[0263]

[0264] As can be seen, surprisingly high Vicat values ​​and particularly high HDT values ​​are achieved for the compositions of the invention. Examples IE1, IE3, IE4 and IE5 also exhibit excellent tensile modulus.

Claims

1. A polypropylene-polyethylene composition having: - melt flow rate MFR2 (230°C, ISO 1133) of 1.5 to 4.0 g / 10 min; - a tensile modulus of at least 1300 MPa measured according to ISO 527-2; - the crystalline fraction (CF) is present in an amount ranging from 90.8 to 93.5 wt.-% relative to the total weight of the polypropylene-polyethylene composition, measured according to Crystex analysis, preferably the Crystex analysis described in the description; - the soluble fraction (SF) is present in an amount ranging from 6.5 to 9.2 wt.-% relative to the total weight of the polypropylene-polyethylene composition, measured according to Crystex analysis, preferably the Crystex analysis described in the description; - the intrinsic viscosity [IV(CF)] of the crystalline fraction measured according to Crystex analysis, preferably the Crystex analysis described in the description, is from 2.3 to 2.9 dl / g; - the intrinsic viscosity [IV(SF)] of the soluble fraction measured according to Crystex analysis, preferably the Crystex analysis described in the specification, is from 1.80 dl / g to 2.40 dl / g; and - a content of units derived from ethylene [C2(CF)] in the crystalline fraction measured according to Crystex analysis, preferably the Crystex analysis described in the description, of 3.0 to 4.8% by weight; in, The polypropylene-polyethylene composition comprises a recycle fraction.

2. The polypropylene-polyethylene composition according to claim 1, wherein The polypropylene-polyethylene composition has a content of units derived from ethylene in the soluble fraction [C2(SF)] of 18.0 to 26.0 wt.-% as measured by Crystex analysis, preferably by Crystex analysis as described in the specification.

3. The polypropylene-polyethylene composition according to claim 1 or 2, wherein The polypropylene-polyethylene composition has one or more of the following: (i) a limonene content of 0.1 ppm to 100 ppm as determined by solid phase microextraction (HS-SPME-GC-MS); (ii) a fatty acid content of 0.1 to 100 ppm as determined by solid phase microextraction (HS-SPME-GC-MS); (iii) a polyamide content of 0.001 to 0.5 wt. % as determined by IR; (iv) a polystyrene content of 0.05 to 0.8 wt % as determined by IR; (v) a talc content of 0.01 to 0.5 wt % as determined by FTIR; (vi) Chalk content of 0.01 to 0.5 wt. % as determined by FTIR.

4. A polypropylene-polyethylene composition according to any one of the preceding claims, wherein The polypropylene-polyethylene composition has: - a tensile modulus of at least 1500 MPa measured according to ISO 527-2; - the intrinsic viscosity [IV(SF)] of the soluble fraction measured according to Crystex analysis, preferably the Crystex analysis described in the specification, is from 1.95 dl / g to 2.40 dl / g; - the content of units derived from ethylene [C2(CF)] in the crystalline fraction measured according to Crystex analysis, preferably the Crystex analysis described in the description, is from 3.0 to 3.9% by weight.

5. A polypropylene-polyethylene composition according to any one of the preceding claims, wherein: The polypropylene-polyethylene composition has: - the content of units derived from ethylene in the soluble fraction [C2(SF)] measured according to Crystex analysis, preferably the Crystex analysis described in the description, is from 22.0 to 26.0% by weight.

6. The polypropylene-polyethylene composition according to claim 1, wherein The polypropylene-polyethylene composition can be obtained by blending the following components in amounts relative to the final polypropylene-polyethylene composition: a) 39 to 70 wt. %, preferably 49 to 70 wt. % of a recycled polypropylene-polyethylene blend (A) having: - the crystalline fraction (CF) is present in an amount of 89.0 to 92.0 wt.-% relative to the total weight of the recycled polypropylene-polyethylene blend (A) measured according to Crystex analysis, preferably the Crystex analysis described in the description; - the soluble fraction (SF) is present in an amount of 8.0 to 11.0 wt.-% relative to the total weight of the recycled polypropylene-polyethylene blend (A) measured according to Crystex analysis, preferably the Crystex analysis described in the description; - the intrinsic viscosity [IV(CF)] of the crystalline fraction measured according to Crystex analysis, preferably the Crystex analysis described in the description, is from 1.50 to 1.80 dl / g; - the intrinsic viscosity [IV(SF)] of the soluble fraction measured according to Crystex analysis, preferably the Crystex analysis described in the specification, is from 0.80 dl / g to 1.80 dl / g; - a content of units derived from ethylene [C2(CF)] in the crystalline fraction measured according to Crystex analysis, preferably the Crystex analysis described in the description, of 4.0 to 8.0% by weight; and - Optionally, the percentage of polyethylene melting enthalpy is lower than 2.5%, preferably lower than 2.1%; and b) 30 to 61 wt.-%, preferably 30 to 51 wt.-% of an original heterophasic propylene copolymer having: - melt flow rate MFR2 (230°C, ISO1133) of 0.15 to 0.35 g / 10 min; - a Young's modulus of at least 1800 MPa, measured in a tensile test according to ISO 527-2 on injection moulded multipurpose specimens prepared according to ISO 527-1; - a content of soluble fraction (SF) measured according to Crystex analysis, preferably the Crystex analysis described in the description, of 3.0 to 8.0 wt.-%, based on the total weight of the original heterophasic propylene copolymer; as well as - a total ethylene (C2) content of 0.5 to 3.0 wt.-% as measured according to Crystex analysis, preferably the Crystex analysis described in the description.

7. The polypropylene-polyethylene composition according to claim 6, wherein The pristine heterophasic propylene copolymer has a Charpy notched impact strength (1eA) (non-instrumented, ISO 179-1, +23°C) of at least 27 kJ / m 2 .

8. The polypropylene-polyethylene composition according to any one of claims 5 to 7, wherein The pristine heterophasic propylene copolymer has an intrinsic viscosity [IV(SF)] of the soluble fraction measured according to Crystex analysis, preferably Crystex analysis as described in the description, of 3.2 to 3.9 dl / g.

9. The polypropylene-polyethylene composition according to any one of claims 5 to 8, wherein The pristine heterophasic propylene copolymer has a content of soluble fraction (SF) measured according to Crystex analysis, preferably the Crystex analysis described in the description, of 4.0 to 7.0 wt.-%, based on the total weight of the pristine heterophasic propylene copolymer.

10. The polypropylene-polyethylene composition according to claim 4, wherein The polypropylene-polyethylene composition can be obtained by blending the following components in amounts relative to the final polypropylene-polyethylene composition: a) 39 to 70 wt. %, preferably 49 to 70 wt. % of a recycled polypropylene-polyethylene blend (A) having: - the crystalline fraction (CF) is present in an amount of 89.0 to 90.7 wt.-% relative to the total weight of the recycled polypropylene-polyethylene blend (A) measured according to Crystex analysis, preferably the Crystex analysis described in the description; - the soluble fraction (SF) is present in an amount of 9.3 to 11.0 wt.-% relative to the total weight of the recycled polypropylene-polyethylene blend (A) measured according to Crystex analysis, preferably the Crystex analysis described in the description; - the intrinsic viscosity [IV(SF)] of the soluble fraction measured according to Crystex analysis, preferably the Crystex analysis described in the specification, is from 1.60 dl / g to 1.80 dl / g; - a content of units derived from ethylene [C2(CF)] in the crystalline fraction measured according to Crystex analysis, preferably the Crystex analysis described in the description, of 4.0 to 4.7% by weight; and - Optionally, the percentage of polyethylene melting enthalpy is lower than 2.5%, preferably lower than 2.1%; and b) 30 to 61 wt.-%, preferably 30 to 51 wt.-% of an original heterophasic propylene copolymer having: - melt flow rate MFR2 (230°C, ISO1133) of 0.15 to 0.35 g / 10 min; - a Young's modulus of at least 1800 MPa, measured in a tensile test according to ISO 527-2 on injection moulded multipurpose specimens prepared according to ISO 527-1; - Charpy notched impact strength (1eA) (non-instrumented, ISO 179-1, +23°C) of at least 27 kJ / m 2 ; - a content of soluble fraction (SF) measured according to Crystex analysis, preferably the Crystex analysis described in the description, of 3.0 to 8.0 wt.-%, based on the total weight of the original heterophasic propylene copolymer; as well as - a total ethylene (C2) content of 0.5 to 3.0 wt.-% as measured according to Crystex analysis, preferably the Crystex analysis described in the description.

11. A method for obtaining a polypropylene-polyethylene composition, comprising the step of blending the following components in amounts relative to the polypropylene-polyethylene composition finally obtained: a) 39 to 70 wt. %, preferably 49 to 70 wt. % of a recycled polypropylene-polyethylene blend (A) having: - the crystalline fraction (CF) is present in an amount of 89.0 to 92.0 wt.-% relative to the total weight of the recycled polypropylene-polyethylene blend (A) measured according to Crystex analysis, preferably the Crystex analysis described in the description; - the soluble fraction (SF) is present in an amount of 8.0 to 11.0 wt.-% relative to the total weight of the recycled polypropylene-polyethylene blend (A) measured according to Crystex analysis, preferably the Crystex analysis described in the description; - the intrinsic viscosity [IV(CF)] of the crystalline fraction measured according to Crystex analysis, preferably the Crystex analysis described in the description, is from 1.50 to 1.80 dl / g; - the intrinsic viscosity of the soluble fraction [IV(SF)] measured according to the Crystex analysis, preferably the Crystex analysis described in the specification; - a content of units derived from ethylene [C2(CF)] in the crystalline fraction measured according to Crystex analysis, preferably the Crystex analysis described in the description, of 4.0 to 8.0% by weight; and b) 30 to 61 wt.-%, preferably 30 to 51 wt.-% of an original heterophasic propylene copolymer having: - melt flow rate MFR2 (230°C, ISO 1133) of 0.15 to 0.35 g / 10 min; - a Young's modulus of at least 1800 MPa, measured in a tensile test according to ISO 527-2 on injection moulded multipurpose specimens prepared according to ISO 527-1; - a content of soluble fraction (SF) measured according to Crystex analysis, preferably the Crystex analysis described in the description, of 3.0 to 8.0 wt.-%, based on the total weight of the original heterophasic propylene copolymer; and - A total ethylene (C2) content of 0.5 to 3.0 wt.-%, based on the total weight of the original heterophasic propylene copolymer, measured according to Crystex analysis, preferably the Crystex analysis described in the description.

12. The method according to claim 11, wherein: The pristine heterophasic propylene copolymer has a Charpy notched impact strength (1eA) (non-instrumented, ISO 179-1, +23°C) of at least 27 kJ / m 2 .

13. A thermoformed article made from the polypropylene-polyethylene composition of any one of claims 1 to 10.

14. A thermoformed article made from the polypropylene-polyethylene composition of any one of claims 1 to 10, said thermoformed article containing at least 97.0% by weight of the polypropylene-polyethylene composition relative to said thermoformed article.

15. The thermoformed article made of the polypropylene-polyethylene composition according to claim 14, wherein: The amount of the polypropylene-polyethylene composition relative to the thermoformed article is at least 98.5 wt%.

Citation Information

Patent Citations

  • Thermoforming tray having recycled polypropylene for oxygen-proof and the manufacturing method thereof

    KR102184015B1

  • Process to produce polypropylene-based composition from post-consumer resins and articles made of said compositions

    WO2019224129A1